Civilizing Generations Through Literacy Learning in Arekan Javanese Culture: A Gerbangkertasusila Perspective - Syihabul Khoir; Dandy Ashghor Dawudi; Darni (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2024)
In the era of society 5.0 which is based on sophisticated information and communication technology, the cultural patterns that exist within generations tend to become increasingly abstract. This gives rise to the urgency of acculturation in the education space in order to maintain cultural integrity as national identity so that it remains strong. This research aims to discuss Javanese cultural literacy learning. The items that will be included in literacy learning are historical elements, art elements, folklore elements. This research uses a qualitative descriptive research method with a project-based instructional design approach. The results of this research were the formulation of two learning designs consisting of a learning design in collaboration with arts and culture teachers for a folklore-based digital comic project and a group instructional learning design to formulate the characters of a folklore. Through this learning design, it is hoped that it can become a means of integrating the nation's cultural identity to prepare a generation with character who is ready to answer the challenges of the times.